APPLICATION OF STATISTICAL QUALITY CONTROL (SQC) TO ENHANCE PRODUCT QUALITY IN THE PRINTING INDUSTRY OF MAKASSAR - Fole, Asrul; Safitri, Khoerun Nisa (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
The printing industry in Makassar faces significant challenges related to product quality, often characterized by a high defect rate. This study aims to enhance product quality by applying Statistical Quality Control (SQC) methods to identify and analyze the root causes of defects, as well as to provide effective improvement recommendations. The methodologies employed include various quality analysis tools such as histograms, Pareto charts, scatter diagrams, control charts, and fishbone diagrams. The findings indicate that the application of SQC successfully identified key defects, including torn materials and unclear prints, along with contributing factors related to human, material, machine, and method aspects. These insights provide a solid foundation for formulating effective corrective actions to improve overall product quality. The impact of this research is a significant enhancement in quality control practices within the printing industry, along with the implementation of best practices that can be adopted by other companies. The conclusions emphasize that the application of SQC is effective in identifying and addressing product defects, enabling companies to develop targeted improvement measures, such as enhancing employee training and selecting higher-quality materials. This research is expected to contribute meaningfully to the advancement of quality control practices in the printing industry and serve as a valuable reference for other companies seeking to improve product quality and production efficiency.